Deficyt budżetowy w Polsce na tle krajów Unii Europejskiej w aspekcie wejścia do strefy euro - Krzemińska, Agnieszka (Budget Deficit in Poland in Comparison with the EU in the Aspect of Going to Monetary Union, 2009)
Poland has been grappling with many problems of budgetary policy for years. It is believed that focal burden is relatively high, complicated and fluctuating. The structure of expenditure does not benefit economy development. Furthermore, the high public debt, which is the result of long-term budget deficit threatens economic and social stability. However, the difficulty to shape the height of deficit is not only Polish problem but it also concerns the EU countries and it is one of the main barriers of development. The aim of this article is to assess to which degree the balance in Poland between 2000 and 2007 is the result of cyclical factors and to which degree structural factors. The analysis is based on several indexes such as the real growth rate of GDP, revenue and expenditure in relation to GDP, nominal revenue and expenditure dynamism, actual balance, cyclical balance, cyclically adjusted balance, primary balance and the comparison of fiscal situation in Poland with that of EU's
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 127-141